Effect of black rice husk ash on asphaltic concrete properties under aging condition - Putra Jaya, Ramadhansyah; Noram Irwan, Ramli; Mohd Khairul Idham, Mohd Satar; N.A., Abdullah; Mohd Rosli, Hainin; Norhidayah, Abdul Hassan; Haryati, Yaacob; Muhammad Naqiuddin, Mohd Warid; A., Mohamed (IOP Publishing, 2018)
The scarcities of natural resources and increment in waste production rates have promoted efforts to investigate the potential incorporation of various by-products in roads construction. Reusing of waste materials such as black rice husk ash (BRHA) in asphaltic concrete was considered as one of the proper management of the waste, which ensures economic and environmental benefits. Hence, this study investigates the effect of black rice husk ash on asphalt mixtures properties under different aging condition. BRHA was added in the asphalt mix in a proportion of 0%, 2%, 4% and 6% by weight of bitumen. 5% optimum bitumen content with 60/70 penetration grade binder was selected for this study. The asphalt mixtures for each fraction was prepared in three different aging conditions i.e. un-aging (UA), short term aging (STA) and long term aging (LTA). The properties of asphalt mixtures were evaluated by voids, stiffness and dynamic creep tests. The results indicate that asphalt mixtures consisting of BRHA have exhibited better performance in term of voids, stiffness and creep modulus when compared to the conventional asphalt mixtures. The STA and LTA mixtures modified with BRHA produced higher performance than the unmodified mixtures. It can be concluded that the optimum additional percentage of BRHA was in the range of 4% to 6%.